THE FUTURE OF ENGLISH LANGUAGE TEACHING AND LEARNING THROUGH “MERDEKA BELAJAR - KAMPUS MERDEKA” (MBKM): A SYSTEMATIC REVIEW - Rigel Sampelolo; Matius Tandi Kombong (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This publication systematically reviews literature on MBKM (Merdeka Belajar – Kampus Merdeka). As MBKM is relatively a new program, its prospects and challenges in its implementation in English language teaching are regarded important to be scholarly-reviewed. In this study, the total of 17 scholarly-published journals were systematically reviewed. The journals included in this study were those published in 2020 and 2021 which set “Merdeka Belajar – Kampus Merdeka” and/or “MBKM” as keywords. The searching was conducted on www.google.co.id. Based on analysis, it is found that all journals appreciate the MBKM programs as promising and innovative. Furthermore, the scholarly-published journals explore the MBKM programs through philosophical basis, its implementation, challenges, and how they are perceived. In addition, the 8 programs and 4 policies are mainly set as the findings. In this publication, the future of English language teaching and learning through 8 programs and 4 policies of “Merdeka Belajar – Kampus Merdeka” is addressed.